Pengetahuan Mahasiswa Tentang Penggunaan Alat Pemadam Api Ringan (APAR) Berhubungan Dengan Sikap Dalam Penanggulangan Kebakaran - Ani Sutriningsih; Rachmat Chusnul Choeron; Stefani Andriani Ndae (Universitas Tribhuwana Tunggadewi, 2021)
Fires can be prevented but the incidence is still quite high so it is important to know how to deal with them, especially in the use of light fire extinguishers (APAR). A fire incident requires a quick response to fire. The purpose of the study was to determine the relationship between students' knowledge about the use of a Light Fire Extinguisher (APAR) with fire prevention attitudes in the Chemistry Laboratory of Unitri Malang. The research design used cross sectional. The sample consisted of students of Chemical Engineering UNITRI Malang in the class of 2019 as many as 53 respondents who were taken using simple random sampling. Collecting data using questionnaires and analyzed by fisher-exact test. The results obtained that respondents have a good level of knowledge category (58.5%) and have a good attitude category (67.9%). Fisher-exact test analysis found that there was a relationship between students' knowledge about the use of fire extinguishers and attitudes in fire prevention. It is hoped that there will be training on the use of fire extinguishers on an ongoing basis and continuous socialization will be carried out after the training so that they can know how to deal with fires